2018
DOI: 10.1007/978-3-030-01168-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Energy Efficient Edge Computing: A Survey

Abstract: Internet of Things is evolving heavily in these times. One of the major obstacle is energy consumption in the IoT devices (sensor nodes and wireless gateways). The IoT devices are often battery powered wireless devices and thus reducing the energy consumption in these devices is essential to lengthen the lifetime of the device without battery change. It is possible to lengthen battery lifetime by efficient but lightweight sensor data analysis in close proximity of the sensor. Performing part of the sensor data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Väänänen and Hämäläinen [52] defined the concepts of edge, fog, cloud and cloud, however, the authors dedicated an entire section to identifying the advantages of Edge Computing. The authors analyzed the benefits of Edge Computing from the perspective of energy efficiency, security, and privacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Väänänen and Hämäläinen [52] defined the concepts of edge, fog, cloud and cloud, however, the authors dedicated an entire section to identifying the advantages of Edge Computing. The authors analyzed the benefits of Edge Computing from the perspective of energy efficiency, security, and privacy.…”
Section: Resultsmentioning
confidence: 99%
“…The research of Väänänen and Hämäläinen [52] analyzed the requirements for energy-efficient Edge Computing. The authors identified multiple challenges when applying edge and fog computing in energy efficiency applications.…”
Section: Related Workmentioning
confidence: 99%
“…It should be considered that NTP protocol consumes many resources and increases latency in industrial environments. In [71] the authors, review the methods used to decrease energy consumption in the WSN sensor networks; The low energy adaptive clustering hierarchy (LEACH) protocol uses some methods and techniques to solve this problem. Modern high-reach and low-consumption IoT networks achieve energy savings using limited bandwidth and intelligent modulation.…”
Section: Energy Consumptionmentioning
confidence: 99%
“…Using some simple and computationally light compression method can be a very effective way to save in energy consumption and thus lengthen the lifetime of battery powered sensor nodes which often operate wirelessly [3].…”
Section: Introductionmentioning
confidence: 99%